THE IMPORTANCE OF RESCUING TRADITIONAL AND CULTURAL DANCES AT SCHOOL: A FOCUS ON AFRO-BRAZILIAN CULTURE (REMUNOM, 2025)
This article analyzes the importance of reviving traditional and cultural dances in the school context, with an emphasis on Afro-Brazilian culture. The proposal aims to understand how traditional dances contribute to the appreciation and preservation of cultural manifestations, promoting diversity and respect for the different cultural origins present in Brazil. The research is based on a bibliographic, exploratory and documentary study, addressing legislation that highlights the relevance of teaching Afro-Brazilian culture in schools. The results show that dance is an effective pedagogical tool to promote citizenship, strengthen identities and preserve cultural traditions. It was observed that the inclusion of Afro-Brazilian dances in schools contributes to the appreciation of culture, combating prejudice and building a more inclusive society. The studies point to the need to expand the use of cultural dances in schools, respecting cultural diversity and valuing Afro-Brazilian culture.